Method of estimation of competitive position of operator of port container terminal on the basis of multidimentional groupings - Savelyeva, I. V. (Science and Transport Progress, 2012)
In developing the strategy for development of port container terminal in the competitive environment, one of the main problems is the method of estimating the competitive position of each port (separate terminals) and ranking them on a number of key indicators that characterize the dynamics of their development. To solve this problem it is necessary to develop scientifically sound and practicable methodology to assess the effectiveness of the provisions of industrial and financial activity of a single terminal.